STRATEGI ORKESTRASI PLATFORM BISNIS PENDIDIKAN ERA NEW NORMAL - Kezia Bunga Indah; Luh Putu Mahyuni (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Online-based education such as e-learning is very useful in today's new normal era. There are several international educational platforms, including those used in this study, namely Coursera, eDX and Future Learn. The purpose of this study was to explore the orchestration strategy of the normal new era education platform business organizers. This study used a qualitative approach was carried out through documentation studies method. This study indicates that the online education business platform implements an orchestration strategy with several different business partner networks. The orchestration strategy is implemented as an integral part of the business model. Through the analysis of The Business Model Canvas, this study finds that the online education business platform has the following business models: 1. Customer Segments, targeting the target group of people; 2. Value Proposition, prioritizing the value offered; 3. Channels, using channels to provide means of communication and information; 4. Customer Relationship, a good relationship with customers; 5. Revenue Streams, a source of income in business; 6. Key resource, in the form of assets of the company; 7. Key Activities, a series of activities; 8. Key Partners, a network of relationships; 9. Cost Structure, all costs incurred to operate the business. Keywords: e-learning, education platform, online course, business model canvas, orchestration